2020
DOI: 10.3389/fphys.2020.00228
|View full text |Cite
|
Sign up to set email alerts
|

Slit2 Protects Hearts Against Ischemia-Reperfusion Injury by Inhibiting Inflammatory Responses and Maintaining Myofilament Contractile Properties

Abstract: Background: The secreted glycoprotein Slit2, previously known as an axon guidance cue, has recently been found to protect tissues in pathological conditions; however, it is unknown whether Slit2 functions in cardiac ischemia-reperfusion (IR) injury. Methods: Langendorff-perfused isolated hearts from Slit2-overexpressing (Slit2-Tg) mice and C57BL/6J mice (background strain) were subjected to 20 min of global ischemia followed by 40 min of reperfusion. We compared Slit2-Tg with C57BL/6J mice in terms of left ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…Hamdani et al ( 23 ) further found that the phosphorylation levels of several titin sites were decreased, accompanied by corresponding changes in the expression levels of protein kinases and phosphatases. Our previous study revealed that myofilament phosphorylation is sensitive to all cardiac stresses ( 19 , 21 ). However, myofilament phosphorylation is quite dynamic during cardiac stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hamdani et al ( 23 ) further found that the phosphorylation levels of several titin sites were decreased, accompanied by corresponding changes in the expression levels of protein kinases and phosphatases. Our previous study revealed that myofilament phosphorylation is sensitive to all cardiac stresses ( 19 , 21 ). However, myofilament phosphorylation is quite dynamic during cardiac stress.…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing was used to profile gene expression following DAC treatment as previously described ( 19 ). Briefly, total RNA was extracted using TRIzol reagent (cat.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathological examinations were conducted to determine the cardiac structure, fibrosis, vessel morphology, and cardiomyocyte size as previously described ( 15 , 22 ). Masson's trichrome staining was performed to identify collagen fibers and muscle tissue, whereas wheat germ agglutinin was used to visualize cardiomyocyte plasma membranes and calculate the cardiomyocyte size.…”
Section: Methodsmentioning
confidence: 99%